2011
DOI: 10.1371/journal.pone.0014632
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the 20q Chromosomal Arm Occurs Early in Tumorigenic Transformation and May Initiate Cancer

Abstract: Duplication of chromosomal arm 20q occurs in prostate, cervical, colon, gastric, bladder, melanoma, pancreas and breast cancer, suggesting that 20q amplification may play a causal role in tumorigenesis. According to an alternative view, chromosomal imbalance is mainly a common side effect of cancer progression. To test whether a specific genomic aberration might serve as a cancer initiating event, we established an in vitro system that models the evolutionary process of early stages of prostate tumor formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 54 publications
7
60
2
Order By: Relevance
“…4F) and nuclear localization (Fig 4D). All together, these results clearly establish PTPN1 as an AR-regulated gene, and corroborate findings of a previous study that reported the co-amplification of PTPN1 and AR in a human prostate cancer xenograft model (39, 40). Interestingly, PTPN1 is located on chromosome 20q13, a region frequently amplified in several tumor types (40).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4F) and nuclear localization (Fig 4D). All together, these results clearly establish PTPN1 as an AR-regulated gene, and corroborate findings of a previous study that reported the co-amplification of PTPN1 and AR in a human prostate cancer xenograft model (39, 40). Interestingly, PTPN1 is located on chromosome 20q13, a region frequently amplified in several tumor types (40).…”
Section: Discussionsupporting
confidence: 91%
“…All together, these results clearly establish PTPN1 as an AR-regulated gene, and corroborate findings of a previous study that reported the co-amplification of PTPN1 and AR in a human prostate cancer xenograft model (39, 40). Interestingly, PTPN1 is located on chromosome 20q13, a region frequently amplified in several tumor types (40). Despite conflicting results that question the relevance of this amplified region in hereditary prostate cancer (41), the fact that PTPN1 is frequently amplified in metastatic tumors as well as in a subset of high-risk primary tumors (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas high level amplifications correlated with tumor progression in breast cancer [37], low-level amplifications appeared to be rather associated with early stage ovarian carcinoma [38]. Similarly, 20q gain also occurred as an early event in normal prostatic cells immortalized by TERT overexpression, where a number of oncogenes in the 20q13.2 region cooperate to support immortalization [39]. Gains at 20q thus appear to represent an early event in the evolution of a  malignant phenotype [39].…”
Section: Discussionmentioning
confidence: 99%
“…The AURKA gene is located in chromosome arm 20q, which is often amplified in many human cancers and contains multiple oncogenes 49 . We examined AURKA amplification in HNSCCs, but this was not associated with the intensity of AURKA staining ( Supplementary Fig.…”
Section: Sa-2xpamentioning
confidence: 99%